Codigestion of food waste and real traditional Chinese medicine wastewater in anaerobic membrane bioreactor: Stability mechanism and microbial community dynamics - Yong-Xin Cui; Bao-Shan Xing; Su Li; Zi-Yi Wang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Surface texture of laser-fabricated helical microgrooves on pressure swirl nozzles for enhanced atomization characteristics - Shenghan Cao; Jianxin Deng; Shiyao Rong; Yichen Bao; Junyan Wang; Zhihui Zhang (Crop Protection, 2026)

Artemselenolides I–N, sesquiterpenoid trimers from Artemisia selengensis with antihepatoma activity – structural elucidation, molecular docking and dynamics studies - Rong-Kai Chen; Tian-Ze Li; Yong-Cui Wang; Yun-Bao Ma; Ji-Jun Chen (Phytochemistry, 2026)

Bacterial cellulose guided In-Situ growth of ZIF-8 toward hierarchical N-doped porous carbon for enhanced CO2 capture - Shijie Wang; Xudong Zheng; Sifan Bao; Zihuai Xu; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Unraveling the short- and long-term effects of lignocellulosic pretreatment derivatives on the anaerobic co-digestion of corn straw and food waste: Digester performance, microbial community, and metabolic mechanisms - Sifan Cao; Yong-Chen Han; Xiaochang C. Wang; Rong Chen; Bao-Shan Xing (Bioresource Technology, 2026)

Carbon cloth-mediated direct interspecies electron transfer effect on the intensification mechanism of high-load codigestion dynamic membrane bioreactors - Bao-Shan Xing; Yi-Fan Wu; Yi Zhang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Associations of serum lithium, nickel, cobalt, and manganese with chronic kidney disease among Chinese older adults: Mediating role of lipid metabolism and moderating effect of lifestyle - Yan Wang; Qingping Liu; Wenyuan Zhu; Xiaoqing Ma; Tao Zhang; Mengqi Zou; Mengruo Wang; Lei Bao; Yaxian Pang; Tao Jing; Rong Zhang (Environmental Pollution, 2026)

Dynamic modeling and numerical simulation of dense particle multiphase flows in resonant acoustic mixing - Jingming Zhang; Mingming Shi; Bao Rong; Gouping Wang; Da Li; Xiaoting Rui (Chemical Engineering Journal, 2026)

Advanced nitrogen removal system coupling partial nitritation, anammox, denitrification and oxygen-permeable hollow-fibre membranes for precise oxygen regulation - Xifang Tang; Bao-Shan Xing; Yong-Ning Feng; Liguo Wan; Ling-Hu Li; Xin-Xin Sun; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Industrial waste salt pyrolysis toward zero liquid discharge: Enabling efficient organic removal and resource recovery - Zhi-Bo Li; Xiang-Lin Chang; Juan Xie; Rong Chen; Xiaochang C. Wang; Bao-Shan Xing (Journal of Water Process Engineering, 2026)

N(7)-methylguanosine modification of mitochondrial tRNA-Trp drives myocardial injury induced by silicon carbide nanoparticles - Qingping Liu; Tao Zhang; Mengruo Wang; Peilin Zheng; Wen Gu; Yujia Xie; Yaxian Pang; Lei Bao; Haijing Zhang; Yujie Niu; Yufei Dai; Rong Zhang (Journal of Hazardous Materials, 2026)

Polystyrene nanoplastics induce neuroinflammation-driven depression-like behaviors in mice via the HIF-1α–NAT10–ac4C-mediated glycolytic activation - Yan Liu; Linpeng Niu; Cunhui Zhang; Lei Bao; Mengruo Wang; Qingping Liu; Hao Liu; Zhaohui Hu; Lili Shi; Yaxian Pang; Rong Zhang; Yujie Niu (Journal of Environmental Sciences, 2026)

Application of optimized hydrothermal, ozone and superalkali pretreatment techniques for qualitative biogas production from corn straw: A comparative assessment - Sifan Cao; Yong-Chen Han; Huqe Farhana; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Fuel, 2026)

Dendrobium devonum juice modulates aroma formation in coffee cherry husks processing: insights into key pathways and flavour enhancement - Wenrui Huang; Zhiting Zhang; Jiawei Tang; Qinghua Chuai; Yinbo Wang; Rong Wang; Yongming Bao; Feng Guo (Food Additives & Contaminants: Part A, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A dual-channel and multi-scale temporal fusion model based on variational mode decomposition for dissolved oxygen prediction - Rong Ma; Yulong Bai; Xiaoxin Yue; Xianbao Tan; Wenjie Bao; Xufeng Wang (Journal of Hydrology, 2026)

Structural characterization and anti-aging mechanism of Codonopsis pilosula polysaccharides - Meiqi Wan; Rong Han; Xiaoai Bao; Yizheng Sun; Hailong Xu; Yanlin Wang; Aihong Zhao; Youbo Zhang (Food Research International, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Genetic basis of pedicellate spikelet masculinization in maize revealed by an advanced maize–teosinte population - Ruifan Bao; Xueying Wang; Junle Wu; Ting Liang; Xiya Hu; Pengxu Meng; Hang Mi; Peng Li; Sijia Yang; Zhiqin Liu; Siyu Lei; Jinyu Yang; et al. (Planta, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Modeling mesoscopic homogenization of bentonite pellet/powder mixture: inclusion of pellet expansion and powder compression deformation effects - Rong-Sheng Deng; Wei-Min Ye; Bao Chen; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Sustained performance and microbial succession in novel artificial rumen system coupling dynamic membrane with methanogenic granules for acid absorption - Xiang-Lin Chang; Bao-Shan Xing; Yu Qin; Juan Xie; Zhi-Bo Li; Xiaochang C. Wang; Rong Chen; Yu-You Li (Bioresource Technology, 2026)

Mechanism of macrophage mitochondrial transfer in CBNPs induced EndMT of pulmonary microvascular endothelial cells - Mengruo Wang; Qian Wang; Qingping Liu; Shanshan Zhang; Yujia Xie; Tao Zhang; Ze Yang; Lei Bao; Yaxian Pang; Dongxing Shi; Jiaji Cheng; Yujie Niu; et al. (Journal of Hazardous Materials, 2026)

Engineering electron-rich Co-doped BaTiO3 with light-driven redox cycles for superior peroxymonosulfate activation - Bao Pan; Rong Xu; Yifan Hao; Jiani Qin; Jiahao Zhang; Chuanyi Wang (Chemical Engineering Journal, 2026)

Total flavonoids from Carthamus tinctorius L. inhibit the liver fibrosis progression via Hippo/YAP pathway - Xiaomei Bao; Xiaolu Zhao; Haisheng Wang; Hongwei Yuan; Rong Jin; Mingqi Li; Yinghe Wang; Yuehong Ma (Journal of Natural Medicines, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Amine modified porous carbon aerogel templated by the natural structure of wood for CO2 capture and selective separation - Zhouzhou Yang; Xudong Zheng; Zihuai Xu; Sifan Bao; Wei Sun; Shijie Wang; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Dual efficient X-ray scintillation and strong second harmonic generation in a single cubic alkane Cu4I4 cluster achieved through organic-inorganic synergistic effect - Bao-Yi Li; Jun-Zhe Li; Wen-Fei Wang; Peng-Kun Wang; Rong Li; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2026)

Anode interface layers constructed in situ by multifunctional carbon dots for ultra-stable aqueous zinc-ion batteries - Qian-Li Ma; Xi-Rong Zhang; Bao-Juan Wang; Hao-Wen Sun; Huan-Ming Xiong (Chemical Engineering Journal, 2026)

Glutamine-hydrolyzing GMP Synthase Gene (guaA) Regulates Siderophore Synthesis in the Nitrogen-fixing Bacterium (NFB) Kosakonia radicincitans GXGL-4A - Er-Xing Wang; Bao-Yun Feng; Ya-Ting Zhang; Meng-Ting Zhang; Lu-Rong Xu; Yan-Wen Xue; Yun-Peng Chen (Current Microbiology, 2026)

Effect of ciprofloxacin on performance, antibiotic resistance genes, and microbial communities in mesophilic anaerobic codigestion enriched with Methanosarcina and a recovery strategy after collapse - Bao-Shan Xing; Yong-Ning Feng; Su Li; Liguo Wan; Yi-Fan Wu; Xiaochang C. Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Erosion rates of yardang landforms downstream of the Peacock River, NW China - Bai Youliang; Bo Li; Jinhong Rong; Hui Chen; Jinming Zheng; Jianshe Liu; Tan Bao; Jiangnan Jin; Chuan Wang (Journal of Sedimentary Environments, 2025)

Biocontrol Effects and Potential Defence Mechanism of Bacillus velezensis JS6-1 Against Fusarium solani-Induced Postharvest Rots in Muskmelon - Yafang He; Jiayi Wei; Fushuang Chen; Ning Wang; Yajie Han; Zifei Wu; Xingwen Wang; Faqiang Zhan; Yingwu Shi; Rong Yang; Huifang Bao (Current Microbiology, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dynamic performance tests and multi-parametric refinement models of high-energy dissipation viscoelastic materials for seismic performance enhancement of engineering structures - Yao-Rong Dong; Zhao-Dong Xu; Lihua Zhu; Bao-Shun Wang; Yang Yang; Yu Cheng (Engineering Structures, 2025)

Chemical constituents of the deep-sea-derived fungus Purpureocillium lilacinum XIA-18 and their chemotaxonomic significance - Bao-Fu Li; Yuan Wang; Zheng-Biao Zou; Rong Chao; Tai-Zong Wu; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Partitioning of evapotranspiration in semi-arid rain-fed farmland using an improved stomatal conductance model - Yongzhi Bao; Tingxi Liu; Limin Duan; Xin Tong; Yixuan Wang; Lina Hao; Rong Hua; V. P. Singh (Irrigation Science, 2025)

Extraction of hydroxy safflower yellow A and anhydroxysafflor yellow B from safflower florets using natural deep eutectic solvents: Optimization, biological activity and molecular docking - Chun-Ying Wu; Bao-Rong Wang; Si-Yi Han; Ying-Hua Zhang; Zhi-Shen Mu (Food Bioscience, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Reduced mixed Ni-Co-Al metal oxide catalysts with rich oxygen vacancy derived from layered double hydrotalcite for selective hydrogenation of furfuryl alcohol to 1,5-Pentanediol - Nan Xi; Qiwang Li; Yi Chen; Ruixi Bao; Qinglian Wang; Yixiong Lin; Jun Yue; Rong Wang; Chen Yang; Wang Yin; Ting Qiu (Chemical Engineering Journal, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Reticulophagy promotes EMT-induced fibrosis in offspring’s lung tissue after maternal exposure to carbon black nanoparticles during gestation by a m5C-dependent manner - Zhe Du; Qingping Liu; Mengruo Wang; Yifu Gao; Qi Li; Yizhe Yang; Tianyu Lu; Lei Bao; Yaxian Pang; Haijun Wang; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2025)

Polyphenolic compounds mitigate the oxidative damage of anammox sludge under long-term light irradiation - Zhi-Qi Ren; Rong-Rong Chang; Hao Wang; Gui-Feng Li; Bao-Cheng Huang; Ren-Cun Jin (Bioresource Technology, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

An auto-configurable and interpretable ensemble learning framework for optimal catalyst design of green methanol production via Bayesian optimization - Dongwen Rong; Zhao Wang; Qiwen Guo; Runjie Bao; Qingchun Yang (Journal of Cleaner Production, 2025)

Selective recovery of Cu and efficient removal of As(V) from Cu electrolyte via four-stage continuous coupled sulfide precipitation - Hao Jin; Linhua Jiang; Ning Duan; Jinyu Wang; Xiaolu Sun; Yong Liu; Guangbin Zhu; Liye Bao; Rong Zhang (Journal of Cleaner Production, 2025)

Isolation, structural elucidation and biosynthetic pathway of bioactive prenyl quinone compounds from Panus lecomtei based on untargeted metabolomics combined with molecular networking - Si-Xian Wang; Bao-Song Chen; Zi-Juan Zhang; Shi-Rong Zhu; Xiao-Ling Wang; Gao-Qiang Liu (Food Chemistry, 2025)

Monoclonal antibody-based lateral flow immunoassay:An alternative solution for the rapid detection of formaldehyde - Lin Luo; Rui Liang; Zhan-Peng Chen; Bao-Zhu Jia; Ai-Fen Ou; Rong-Rong Zhan; Hong Wang; Hong-Tao Lei; Zhen-Lin Xu (Food Bioscience, 2025)

Simulation of homogenization behavior of compacted bentonite containing technological voids using modified penalty-based contact model - Rong-Sheng Deng; Bao Chen; Wei-Min Ye; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Comparison of molecular testing methods for diagnosing non-tuberculous mycobacterial infections - Leilei Wang; Yu Chen; Qingqing Wang; Jue Pan; Rong Bao; Wenting Jin; Yumeng Yao; Tingting Fang; Na Li; Sichun Luan; Xiaoyu Yin; Le Qin; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Identification and segregation of two closely linked major QTLs for kernel row number in advanced maize–teosinte populations - Jixing Ni; Dengguo Tang; Zhengjie Chen; Sijia Yang; Xueying Wang; Zhiqin Liu; Wujiao Deng; Haimei Wu; Chong You; Jinchang Yang; Pengxu Meng; Ruifan Bao; et al. (Theoretical and Applied Genetics, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Impact of a Potent Strain of Plant Growth-Promoting Bacteria (PGPB), Bacillus subtilis S1 on Bacterial Community Composition, Enzymatic Activity, and Nitrogen Content in Cucumber Rhizosphere Soils - Meng-Ting Zhang; Yu-Qing Bao; Bao-Yun Feng; Lu-Rong Xu; Ya-Ting Zhang; Er-Xing Wang; Yun-Peng Chen (Current Microbiology, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Gas6-Axl signal promotes indoor VOCs exposure-induced pulmonary fibrosis via pulmonary microvascular endothelial cells–fibroblasts cross-talk - Qingping Liu; Yong Niu; Zijie Pei; Yizhe Yang; Yujia Xie; Mengruo Wang; Jingyuan Wang; Mengqi Wu; Jie Zheng; Peihao Yang; Haiyan Hao; Yaxian Pang; et al. (Journal of Hazardous Materials, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

A compound enzyme as an additive to a continuous anaerobic dynamic membrane bioreactor for enhanced lignocellulose removal from codigestion: Performance, membrane characteristics and microorganisms - Bao-Shan Xing; Xiang-Lin Chang; Yi Zhang; Sifan Cao; Xi-Fang Tang; Yong-Chen Han; Yu-You Li; Xiaochang C. Wang; Rong Chen (Bioresource Technology, 2024)

Tanshinone IIA is superior to paricalcitol in ameliorating tubulointerstitial fibrosis through regulation of VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy - Jing-Yi Zeng; Yu Wang; Fu-Yuan Hong; Miao Miao; Yu-Ying Jiang; Zi-Xuan Qiao; Yun-Tao Wang; Xiao-Rong Bao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Glomerulosclerosis and tubulointerstitial fibrosis (TIF) are closely involved in the development of diabetic nephropathy (DN). Moreover, the development of TIF is closely related to epithelial-to-mesenchymal transition (EMT). Tanshinone IIA (Tan) has various pharmacological effects, especially the anti-fibrotic effect. And it is mainly used in the clinical treatment of cardiovascular diseases. Currently, the protective effect of Tan on DN and its possible mechanism have not been clearly elucidated. Our previous studies illustrated that Tan could improve the EMT of HK-2 cells induced by high glucose by regulating the vitamin D receptor (VDR)/Wnt/β-catenin pathway. Here, we collected demographic information and laboratory results from the National Health and Nutrition Examination Survey (NHANES) database in order to investigate the relationship between VD and DN. Then, we established a DN model and treated DN rats with Tan and paricalcitol (Par) for 6 weeks. We subsequently compared the changes in general condition, renal function, pathological changes, and TIF-related protein expression levels of control rats, DN rats induced by STZ, DN rats with Tan at 5.4 mg/kg, DN rats with Tan at 10.8 mg/kg, and DN rats with Par at 0.054 µg/kg, to explore the effect and mechanism of Tan and Par on DN rats. The results showed that VD had a protective effect against DN in diabetic patients. And we found that Tan had a protective effect on renal fibrosis in DN rats, which was superior to Par in improving the symptoms of “three more and one less,” reducing fasting blood glucose level, improving renal index, BUN/SCr, and UACR, reducing histopathological damage of kidney, and improving the expression of fibrosis-related proteins in kidney tissue by regulating VDR/Wnt/β-catenin pathway. Tan was superior to Par in ameliorating tubulointerstitial fibrosis by regulating VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy.

The interactions of subcellular organelles in pulmonary fibrosis induced by carbon black nanoparticles: a comprehensive review - Lei Bao; Qingping Liu; Jingyuan Wang; Lili Shi; Yaxian Pang; Yujie Niu; Rong Zhang (Archives of Toxicology, 2024)

New diterpenoid alkaloids from Delphinium pachycentrum Hemsl - Yuan-Feng Yan; Ya-Rong Wang; Hong-Jun Jiang; Zong-Bao Ding; Tian-Peng Yin (Natural Product Research, 2024)

A literature review on phosphate removal from wastewater by lanthanum-based adsorbents: From mechanisms to applications - Yao-Yao Lu; Hao Wang; Rong-Rong Chang; Wen-Bing Li; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

Use of machine learning to identify key factors regulating volatilization of semi-volatile organic chemicals from soil to air - Rong Wang; Kai-Hui Zhang; Yu Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2024)

Electrospinning-assisted construction of rapid proton conduction channels in halloysite nanotube-encapsulated ionic liquid-embedded sulfonated poly(ether ether ketone) proton exchange membranes - Chunyong Xiong; Zhiwei Ling; Bei Wang; Yang Yu; Qingting Liu; Xudong Fu; Chonggang Wu; Rong Zhang; Shengfei Hu; Xujin Bao; Jun Yang (Fuel, 2024)

A robust Zr(IV)-based metal-organic framework featuring high-density free carboxylic groups for efficient uranium recovery - Bin Wang; Chunyu Bao; Jiahui Xu; Yunnan Tao; Long Chen; Duo Zhang; Kui Tan; Shuao Wang; Jian-Rong Li; Shengqian Ma (Chemical Engineering Journal, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

Hub gene ELK3-mediated reprogramming lipid metabolism regulates phenotypic switching of pulmonary artery smooth muscle cells to develop pulmonary arterial hypertension induced by PM2.5 - Qingping Liu; Yizhe Yang; Mengqi Wu; Mengruo Wang; Peihao Yang; Jie Zheng; Zhe Du; Yaxian Pang; Lei Bao; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2024)

circRNAs deregulation in exosomes derived from BEAS-2B cells is associated with vascular stiffness induced by PM2.5 - Qingping Liu; Yaling Zhang; Bin Han; Mengruo Wang; Huaifang Hu; Jie Ning; Wentao Hu; Meiyu Chen; Yaxian Pang; Yuanyuan Chen; Lei Bao; Yujie Niu; et al. (Journal of Environmental Sciences, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Amino-modified biochar-silica hybrid aerogels with ordered pore structure templated by cellulose nanocrystals for highly efficient and selective CO2 capture - Biao Ji; Xudong Zheng; Zihuai Xu; Sifan Bao; Junwei Wang; Wenyu Weng; Jian Rong; Zhongyu Li (Journal of Cleaner Production, 2024)

Accelerated aging of lithium-ion batteries: bridging battery aging analysis and operational lifetime prediction - Rui Li; Liying Bao; Lai Chen; Cheng Zha; Jingyang Dong; Nan Qi; Rui Tang; Yun Lu; Meng Wang; Rong Huang; Kang Yan; Yuefeng Su; et al. (Science Bulletin, 2023)

OsTKPR1 proteins with a single amino acid substitution fail the synthesis of a specific sporopollenin precursor and cause abnormal exine and pollen development in rice - Feng Liu; Huiting Yang; Rong Tang; Wang Wang; Haodong Shen; Mengxue Xu; Tiancheng Hao; Yuanyuan Hu; Yunhui Zhang; Yiqun Bao (Plant Science, 2023)

Development and analysis of a universal label-free micro/nano component for three-channel detection of silver ions, mercury ions, and tetracycline - Luhui Wang; Mengyang Hu; Rong Liu; Sunfan Xi; Meng Cheng; Yangyinchun Bao; Na Wang; Yafei Dong (Analytica Chimica Acta, 2023)

Effects of organic carbon/elemental carbon and particle size on inhalation bioaccessibility of particle-bound PAHs - Chun-Xue Tang; Ying Dong; Xiao-Yu Yuan; Rong Wang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Science of The Total Environment, 2023)

Site-specific Atg13 methylation-mediated autophagy regulates epithelial inflammation in PM2.5-induced pulmonary fibrosis - Jie Ning; Zijie Pei; Mengruo Wang; Huaifang Hu; Meiyu Chen; Qingping Liu; Mengqi Wu; Peihao Yang; Zihan Geng; Jie Zheng; Zhe Du; Wentao Hu; et al. (Journal of Hazardous Materials, 2023)

An anaerobic dynamic membrane bioreactor (AnDMBR) system enhanced the biogas conversion efficiency and stability of mesophilic codigestion with waste activated sludge and food waste - Bao-Shan Xing; Yi Zhang; Rui-Qi Zhang; Jing Ma; Xiang-Lin Chang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Chemical Engineering Journal, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Long-term in-situ starvation and reactivation of co-digestion with food waste and corn straw in a continuous AnDMBR: Performance, sludge characteristics, and microorganism community - Bao-Shan Xing; Xiang-Lin Chang; Sifan Cao; Dong Wu; Yi Zhang; Xi-Fang Tang; Yu-You Li; Xiaochang C. Wang; Rong Chen (Science of The Total Environment, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Optimization of the induction, germination, and plant regeneration system for somatic embryos in apomictic walnut (Juglans regia L.) - Hongcheng Fang; Yuhui Dong; Rui Zhou; Qingpeng Wang; Qicheng Duan; Changxi Wang; Yan Bao; Shengyi Xu; Xinya Lang; Shasha Gai; Rong Chen; Ke Qiang Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Impacts of Human Activities and Climate Change on Water Storage Changes in Shandong Province, China - Longyun Deng; Zhen Han; Weixing Pu; Rong Bao; Zheye Wang; Quanyuan Wu; Jianmin Qiao (Environmental Science and Pollution Research, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Phenomic and metabolomic responses of roots to cadmium reveal contrasting resistance strategies in two rice cultivars (Oryza sativa L.) - Chong Liu; Mo-ming Lan; Er-kai He; Ai-jun Yao; Guo-bao Wang; Ye-tao Tang; Rong-liang Qiu (Soil Ecology Letters, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Development of Climate and Earth System Models in China: Past Achievements and New CMIP6 Results - Tianjun Zhou; Ziming Chen; Liwei Zou; Xiaolong Chen; Yongqiang Yu; Bin Wang; Qing Bao; Ying Bao; Jian Cao; Bian He; Shuai Hu; Lijuan Li; et al. (Journal of Meteorological Research, 2020)

Pericarp and seed of litchi and longan fruits: constituent, extraction, bioactive activity, and potential utilization - Xiang-rong Zhu; Hui Wang; Jian Sun; Bao Yang; Xue-wu Duan; Yue-ming Jiang (Journal of Zhejiang University-SCIENCE B, 2019)

Effects of NaCl stress on growth of Portulaca oleracea and underlying mechanisms - Jin-Cheng Xing; Jing Dong; Mao-Wen Wang; Chong Liu; Bao-Quan Zhao; Zhu-Gui Wen; Xiao-Mei Zhu; Hai-Rong Ding; Xiao-Hui Zhao; Li-Zhou Hong (Brazilian Journal of Botany, 2019)

Study on the grossular rabbit with high hardness excavated from Yin Ruins, Anyang, China - Rong Wang; Lu Cai; Tian-tian Bao; Ji-gen Tang; Chang-sui Wang (Archaeological and Anthropological Sciences, 2019)

Endogenous Hydrogen Sulfide Promotes Apoptosis via Mitochondrial Pathways in the Livers of Broilers with Selenium Deficiency Exudative Diathesis Disease - Shu-fang Zheng; Rong-kun Bao; Qiao-jian Zhang; Sheng-chen Wang; Hong-jin Lin (Biological Trace Element Research, 2018)

Soil nutrients in relation to vertical roots distribution in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Jin-ming Hu; Yu-hai Bao; Fei Wang; Xiu-bin He (Journal of Mountain Science, 2018)

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells - Ke-Di Wang; Dong-Jiang Xu; Bao-Ya Wang; Dong-Hui Yan; Zhi Lv; Jian-Rong Su (Probiotics and Antimicrobial Proteins, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Selenium protects against cadmium-induced kidney apoptosis in chickens by activating the PI3K/AKT/Bcl-2 signaling pathway - Rong-kun Bao; Shu-fang Zheng; Xin-yue Wang (Environmental Science and Pollution Research, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Bispectral index-guided sedation in transfemoral transcatheter aortic valve implantation: a retrospective control study - Wei He; Rong-rong Huang; Qing-yu Shi; Xian-bao Liu; Jian-an Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Personal exposure to PM2.5 associated with heavy metals in four travel modes of Tianjin during the summer season - Bao Qing Wang; Jian Feng Liu; Bo Wei Liu; Hong Hong Niu; Rong Hui Chen; Ze Bei Wang; Jia Jia Zhao; Zi Hui Ren (Environmental Science and Pollution Research, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Concentrations, properties, and health risk of PM2.5 in the Tianjin City subway system - Bao-Qing Wang; Jian-Feng Liu; Zi-Hui Ren; Rong-Hui Chen (Environmental Science and Pollution Research, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

High precision in-situ Pb isotopic analysis of sulfide minerals by femtosecond laser ablation multi-collector inductively coupled plasma mass spectrometry - HongLin Yuan; Cong Yin; Xu Liu; KaiYun Chen; ZhiAn Bao; ChunLei Zong; MenNing Dai; ShaoCong Lai; Rong Wang; ShaoYong Jiang (Science China Earth Sciences, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Mapping quantitative trait loci (QTL) determining seed-shattering in weedy rice: evolution of seed shattering in weedy rice through de-domestication - Nan Yao; Lei Wang; Huanxin Yan; Yongsheng Liu; Bao-Rong Lu (Euphytica, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Response profiles of cytokines and chemokines against avian H9N2 influenza virus within the mouse lung - Rong Huang; Jiyuan Liu; Wei Liang; Airong Wang; Zhihao Liu; Yan Yang; Jing Lv; Ying Bao; Yanxia Gao; Zengmin Miao; Tongjie Chai (Medical Microbiology and Immunology, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Cerebral vasculopathy in a Chinese family with neurofibromatosis type I mutation - Jian-Tao Liang; Li-Rong Huo; Yu-Hai Bao; Zhen-Yu Wang; Feng Ling (Neuroscience Bulletin, 2013)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Physical characteristics of Chinese Hakka - LianBin Zheng; YongLan Li; ShunHua Lu; JinPing Bao; Yang Wang; XiaoRui Zhang; Hong Xue; WenGuo Rong (Science China Life Sciences, 2013)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Mimic peptides bonding specifically with the first and second extracellular loops of the CC chemokine receptor 5 derived from a phage display peptide library are potent inhibitors of experimental autoimmune encephalomyelitis - Hui-min Zheng; Yun Jiang; Ju-rong Wang; Xue-lian Gong; Bao-yu Guo (Inflammation Research, 2011)

Enhanced yield performance of Bt rice under target-insect attacks: implications for field insect management - Hui Xia; Bao-Rong Lu; Kai Xu; Wei Wang; Xiao Yang; Chao Yang; Ju Luo; Fengxiang Lai; Wenli Ye; Qiang Fu (Transgenic Research, 2011)

Synthesis, Characterization, DNA Binding Properties and Antioxidant Activity of Ln(III) Complexes with Schiff Base Ligand Derived from 3-Carbaldehyde Chromone and Aminophenazone - Yong Li; Zheng-yin Yang; Tian-rong Li; Zeng-chen Liu; Bao-dui Wang (Journal of Fluorescence, 2011)

Differentiation and distribution of indica and japonica rice varieties along the altitude gradients in Yunnan Province of China as revealed by InDel molecular markers - Zhiyuan Xiong; Shujie Zhang; Yunyue Wang; Brian V. Ford-Lloyd; Min Tu; Xin Jin; Yue Wu; Huanxin Yan; Xiao Yang; Ping Liu; Bao-Rong Lu (Genetic Resources and Crop Evolution, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Normal expression of insect-resistant transgene in progeny of common wild rice crossed with genetically modified rice: its implication in ecological biosafety assessment - Hui Xia; Bao-Rong Lu; Jun Su; Rui Chen; Jun Rong; Zhiping Song; Feng Wang (Theoretical and Applied Genetics, 2009)

Responses of Fusarium oxysporum f. sp. niveum to exogenously added sinapic acid in vitro - Hong-sheng Wu; Yang Wang; Wei Bao; Dong-yang Liu; Waseem Raza; Qi-wei Huang; Ze-sheng Mao; Qi-rong Shen (Biology and Fertility of Soils, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

An insulinoma with clinical and electroencephalographic features resembling complex partial seizures - Shuang Wang; Hai-tao Hu; Shu-qun Wen; Zhong-jin Wang; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Abundant Within-varietal Genetic Diversity in Rice Germplasm from Yunnan Province of China Revealed by SSR Fingerprints - Min Tu; Bao-Rong Lu; Youyong Zhu; Yunyue Wang (Biochemical Genetics, 2007)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Glucosamine sulfate–induced apoptosis in chronic myelogenous leukemia K562 cells is associated with translocation of cathepsin D and downregulation of Bcl-xL - Zhe Wang; Rong Liang; Gao-Sheng Huang; Ying Piao; Yong-Qing Zhang; Ai-Qin Wang; Bao-Xia Dong; Ji-Liang Feng; Guo-Rong Yang; Ying Guo (Apoptosis, 2006)